2018
DOI: 10.1093/humrep/dey003
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet and IVF success rate among non-obese women attempting fertility

Abstract: NCT03050944.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 35 publications
2
136
1
1
Order By: Relevance
“…This is reflected in the questions reported by patients in our study, with a special interest on the impact of diet on infertility and its treatment (ranked third). Although recent published studies about diet and fertility (Chiu, Chavarro et al 2018;Nassan, Chavarro et al 2018) and different diet patterns and IVF outcomes indicate a keen interest in this topic (Karayiannis, Kontogianni et al 2018;Sugawa, Okubo et al 2018), in our survey the relative importance of diet appears unexpectedly high. This could be due to the relatively low difficulty in modifying this factor, for example by introducing food supplements or so called "superfoods", in comparison to other lifestyle changes more difficult to maintain, such as changing unhealthy habits or introducing regular physical activity in one's routine.…”
Section: Discussionmentioning
confidence: 60%
“…This is reflected in the questions reported by patients in our study, with a special interest on the impact of diet on infertility and its treatment (ranked third). Although recent published studies about diet and fertility (Chiu, Chavarro et al 2018;Nassan, Chavarro et al 2018) and different diet patterns and IVF outcomes indicate a keen interest in this topic (Karayiannis, Kontogianni et al 2018;Sugawa, Okubo et al 2018), in our survey the relative importance of diet appears unexpectedly high. This could be due to the relatively low difficulty in modifying this factor, for example by introducing food supplements or so called "superfoods", in comparison to other lifestyle changes more difficult to maintain, such as changing unhealthy habits or introducing regular physical activity in one's routine.…”
Section: Discussionmentioning
confidence: 60%
“…The effectiveness of such an intervention was discredited by Bhattacharya et al 15 who reported that a total of 33 ICSI cycles would have to be carried out to prevent one case of total fertilisation failure. Considering the financial burden of some IVF adjuncts14 and the physiological risks of others,3 it is difficult to justify implementing them in clinical practice to patient advantage, while something as simple as adherence to a healthy Mediterranean diet might have the potential to double their chances of IVF success 16. Thus, if the main aim of treatment is to truly benefit the patient, then clinicians should prioritise what is most impactful and beneficial, even if that may be dietary advice and not a sophisticated IVF tool.…”
Section: Beneficencementioning
confidence: 99%
“…Confirmation of the relationship between diet and reproductive fitness also comes from studies reporting a positive effect of the Mediterranean diet (MedDiet) on the semen quality of male partners of couples attempting fertility treatment, and on in vitro fertilization (IVF) success rates among non-obese women [5,6].…”
Section: Dietary Habits and Human Reproductionmentioning
confidence: 99%